THE ROLE OF IRONY IN A LANGUAGE SYSTEM КИНОЯНИНГ ТИЛ ТИЗИМИДА ТУТГАН ЎРНИ - Parmonov, Alisher (Журнал иностранных языков и лингвистики, 2021)
The article describes the linguistic occurrence of the irony and its role in a language system